2008
DOI: 10.1063/1.2838222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electromagnetic performance of brushless motors having magnets in stator and rotor

Abstract: The electromagnetic performance of two permanent magnet brushless motors, viz., flux-switching magnet (FSPM) and surface-mounted motors, in which concentrated stator windings are employed but the magnets are located in the stator and the rotor, respectively, is investigated by the finite element analysis. The significant differences in topologies and static characteristics are highlighted. The results show that both motors exhibit sinusoidal back-emf waveform and the FSPM motor exhibits not only larger airgap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…It can be found the real current waveforms are very close to sinusoidal distribution, realizing the stator-flux orientation vector control. In addition, it also can be found that the torque ripple of the FSPM motor is unfavorably severe which is mostly caused by the large cogging torque [2], [6], [20]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found the real current waveforms are very close to sinusoidal distribution, realizing the stator-flux orientation vector control. In addition, it also can be found that the torque ripple of the FSPM motor is unfavorably severe which is mostly caused by the large cogging torque [2], [6], [20]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although in [20] the results from a comparison between the FSPM motor and the widely-used surface-mounted PM motor indicate that the torque capability of the FSPM motor is slightly superior, however, compared with the conventional rotor-PM counterparts which have been studied and used indepth and maturely, it is far away for the DSPM and FSPM motors to be acceptable in the industrial applications due to the insufficient references on the two new brushless machines. Hence, in this paper, to reveal the advantages and disadvantages of the FSPM machine and DSPM machines further, a comprehensive comparison and evaluation between the two machines are investigated especially on the torque capability.…”
Section: Introductionmentioning
confidence: 88%
“…There are no magnets in the rotor that can be easily skewed to alter the back-EMF [72]. PMFSM topology exhibits torque density similar to that of a fractional-slot PM machine, which is much higher than that of the DSPM [73]. A novel E-core hybrid-excited PMFSM is proposed, which has fewer magnets and a higher torque density than a conventional PMFSM [74].…”
Section: Permanent Magnets On Statormentioning
confidence: 95%
“…Because of the lack of high energy density magnet material this design has not further been investigated in the past. However, in recent years much literature has been published concerning the FSPM because of its superior torque capability and high efficiency which are both comparable to permanent magnet synchronous machines (PMSM) with concentrated windings [2]. The design concept of the FSPM facilitates the cooling of the permanent magnets (PMs) which are integrated in the stator and therefore torque loss due to thermal demagnetization can be easier prevented than in rotor PM machines.…”
Section: Introductionmentioning
confidence: 99%